2000
DOI: 10.1074/jbc.275.19.14760
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sphingomyelin Hydrolysis and Resynthesis on the Activation of NF-κB in Normal and SV40-transformed Human Fibroblasts

Abstract: The precise role of ceramide in NF-B signaling remains unclear. The recent observation of differential sphingomyelin synthase (SMS) activity in normal (low SMS) versus SV40-transformed (high SMS) WI38 human lung fibroblasts provides an opportunity to assess the involvement of ceramide and SMS in NF-B activation. Treatment of normal WI38 fibroblasts with bacterial sphingomyelinase resulted in a 4-fold elevation of ceramide and blocked NF-B activation by serum stimulation. Such inhibition was not observed in SV4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 31 publications
4
61
1
Order By: Relevance
“…Indeed, it has been reported that downregulation of SMS1 reduces the amount of SM in lipid rafts and reduces the rate of cell apoptosis induced by alkyl-lysophospholipid (10). It has also been reported that D609 exposure inhibits TNF-a- (27,14) or phorbol ester-mediated (14) NFkB activity. A critical question remains to be answered: are both SMS1 and SMS2 responsible for the production of plasma membrane-associated SM?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been reported that downregulation of SMS1 reduces the amount of SM in lipid rafts and reduces the rate of cell apoptosis induced by alkyl-lysophospholipid (10). It has also been reported that D609 exposure inhibits TNF-a- (27,14) or phorbol ester-mediated (14) NFkB activity. A critical question remains to be answered: are both SMS1 and SMS2 responsible for the production of plasma membrane-associated SM?…”
Section: Discussionmentioning
confidence: 99%
“…Whether the DAG generated by SMS regulates cellular processes is, in fact, not known. In mammalian cells, SMS activation correlates with the activation and nuclear translocation of NFkB (14); these events are often regulated by DAG-dependent PKC (15). Cerbon and del Carmen Lopez-Sanchez (16) reported that exposure to D609 (an SMS inhibitor) significantly reduces cellular DAG levels, thereby reducing cell proliferation.…”
mentioning
confidence: 99%
“…In this respect, it is worth noting that SM synthase recently emerged as a negative regulator of endogenous ceramide levels involved in signaling processes (35)(36)(37). Moreover, it has been demonstrated that SV40-transformed lung fibroblasts contain a significantly higher SM synthase activity than normal lung fibroblasts, and a role for SM synthase in the regulation of cell growth has been suggested (23).…”
Section: Discussionmentioning
confidence: 99%
“…It also was reported that the activity of GC synthase, which converts ceramide to GC, was more increased in apoptosis-resistant cells than in apoptosis-sensitive cells (12)(13)(14). The involvement of SM synthase in nuclear factor B activation of transformed fibroblast and basic fibroblast growth factor-induced proliferation of primary astrocytes was suggested recently, but the implication of SM synthase has yet to be clarified in Fas-induced apoptosis (15,16).…”
Section: Introductionmentioning
confidence: 99%